Conceptualizing Climate Diplomacy in the Context of Central Asia's Water Challenges (International relations and international law Journal, 2025)
The article analyzes the conceptualization of climate diplomacy in the context of the Central Asian water problem. This region is characterized by high vulnerability to the effects of climate change, hydrological stress and ongoing geopolitical tensions. Based on a combination of theoretical approaches in the field of international relations and environmental management, climate diplomacy is considered both an analytical tool and a practical mechanism for understanding and resolving transboundary water disputes. The results of the study show that climate change is exacerbating the existing water challenges in the region due to melting glaciers, increasing droughts and increasing seasonal water scarcity. The theoretical analysis demonstrates that constructivism, institutionalism, and the theory of international regimes make it possible to explain the transformation of models of cooperation and contradictions in Central Asia, while simultaneously identifying the limitations of existing analytical and practical approaches. The article proposes to form a regional conceptual model of climate diplomacy, which will integrate the principles of environmental safety, sustainable development and management of transboundary water resources. This model considers climate diplomacy not only as a mechanism for conflict prevention and mitigation, but also as a platform for strengthening collective resilience and promoting regional cooperation. The analysis makes both a theoretical contribution to the development of the discourse on climate diplomacy and applied recommendations for improving cooperation between the Central Asian states and external actors.Keywords: climate diplomacy, Central Asia, water challenges, water governance, environmental security.